Penentuan Rasio Keuangan terhadap Harga Saham pada Perusahaan Industri Barang Konsumsi dengan Korelasi terhadap Inflasi Tahun 2015-2022 - Ningsih, Alifvia Ryadi; Riyardi, Agung (Asian Journal of Science, Technology, Engineering, and Art, 2024)
This study focuses on understanding the influence of financial ratios such as current ratio, capital structure (DER), and Firm Size on the stock prices of consumer goods industry companies from 2015 to 2022. Additionally, the stock prices of these companies will be correlated with inflation. The independent variables in this study include current ratio, capital structure (DER), and Firm Size, while the variables correlated with inflation and the dependent variable are the Stock Prices. The sampling method employed is purposive sampling, gathering a sample of 100 instances from 40 companies. The methodology used involves panel data regression utilizing the Random Effect model. The analysis results indicates that the independent variable Current Ratio significantly affects Stock Prices. However, variables like Capital Structure (DER) and Firm Size do not exhibit a significant influence on Stock Prices. Furthermore, Inflation has a significant negative impact on Stock Prices.